Towards a model of contemporary parenting: The parenting behaviours and dimensions questionnaire - Reid, C.; Roberts, Lynne; Roberts, C.; Piek, Jan (Public Library of Science, 2015)
The assessment of parenting has been problematic due to theoretical disagreement, concerns over generalisability, and problems with the psychometric properties of current parenting measures. The aim of this study was to develop a comprehensive, psychometrically sound self-report parenting measure for use with parents of preadolescent children, and to use this empirical scale development process to identify the core dimensions of contemporary parenting behaviour. Following item generation and parent review, 846 parents completed an online survey comprising 116 parenting items. Exploratory and confirmatory factor analyses supported a six factor parenting model, comprising Emotional Warmth, Punitive Discipline, Anxious Intrusiveness, Autonomy Support, Permissive Discipline and Democratic Discipline. This measure will allow for the comprehensive and consistent assessment of parenting in future research and practice.